Kondisi Akuntabilitas dan Transparansi dalam Penerbitan Ijin Gangguan untuk Factory Outlet di Kota Bandung - Gianti Sumarahati; Akino Midhany Tahir (Journal of Regional and City Planning, 2004)
The issuance of Hinder Ordonantie (HO "” Nuisance Act) for non-conforming location of Factory Outlet apparently has generated negative externalities to the public. As a result, Nuisance Act has not been an effective too to control the commercial activities from generating undesirable negative externalities to the public. It is expected that the implementation of accountability and transparency principles from good governance, in the mechanism of issuance will increase its effectiveness. Based on an assessment of accountability and transparency of HO's issuance mechanism it is found that the entrepreneur 's knowledge about HO is limited to only administrative procedure without understanding the technical, retribution, and regulation aspects of HO. The ownership of HO has little meaning but just a formality, showing the legal status of FO activities